Nickel interlayer on the microstructure and property of TC6 to copper alloy diffusion bonding - Gao, Linfeng (2020)
In the present study, diffusion bonding of two dissimilar materials TC6 and copper alloy was investigated in vacuum chamber by directly bonding and using Ni foil as interlayer. Interface quality of the joints was evaluated by mechanical property and microstructure. The maximum shear strength of directly bonding was found to be 64 MPa for the speciemen bonded at 850 °C, 5 MPa for 30 min; and the maximum shear strength with Ni foil interlayer was 113 MPa under the same bonding parameters. The bonding interfaces and fracture surfaces were analyzed by energy disperse spectrometer, scanning electron microscopy and X-ray diffraction. The results show that the diffusion region of directly bonding specimen generated several IMCs (Ti2Cu and Ti5CuSn3, etc.). Fracture morphology showed that brittle fracture present at the Ti5CuSn3 IMCs, which was the weak point of the joint. While the diffusion zone of the specimen with Ni foil interlayer consists of various phase including Ti2Ni, TiNi, TiNi3 at TC6 side, and Cu-Ni solid solution at ZQSn11-4-3 side, and fracture surface of joint present a mixture of brittle and ductile characteristics, and fracture initiated at the TiNi3/Ni interface.